If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = -2 + -3(4 + -2k) -2 = -2 + (4 * -3 + -2k * -3) -2 = -2 + (-12 + 6k) Combine like terms: -2 + -12 = -14 -2 = -14 + 6k Solving -2 = -14 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. -2 + -6k = -14 + 6k + -6k Combine like terms: 6k + -6k = 0 -2 + -6k = -14 + 0 -2 + -6k = -14 Add '2' to each side of the equation. -2 + 2 + -6k = -14 + 2 Combine like terms: -2 + 2 = 0 0 + -6k = -14 + 2 -6k = -14 + 2 Combine like terms: -14 + 2 = -12 -6k = -12 Divide each side by '-6'. k = 2 Simplifying k = 2
| 10k+3=8k+27 | | 72=6(-2+7x) | | 55=18+0.004x | | 32=4(1-7k) | | 2a+4a-13=47 | | 4x-6=3x+1-x-7 | | -5(3x+4)=2(9-6x) | | -36=6X-12Y | | 384628x+298473=2937474 | | 6(5-7n)=72 | | -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x | | y=4865x+1996559th | | b/16=4 | | 11t+4(1-4t)= | | 27=16+n | | 4t-10/5 | | 3n+8=5(n-5)+6 | | b+-17=-31 | | -9*5-4Y=36 | | x^2-2dx-y^2=0 | | 15=n/2 | | -9*3-4Y=36 | | (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 | | 3*4-6Y=-18 | | 0.4x-0.7x-20=1 | | 16(1/2x)^4 | | 5(2m+1)=4m+12 | | (1-8/9)/((1/5)/9+2/9) |